2002
DOI: 10.1051/agro:2002064
|View full text |Cite
|
Sign up to set email alerts
|

Which decision support tools for the environmental management of nitrogen?

Abstract: -Which decision support tools should be developed to help agricultural stakeholders manage nitrogen in an environmentally friendly way? This paper presents the limitations of current decision support tools with respect to the implementation of a four-step quality spiral. PLAN: planning technical actions that satisfy both economic and environmental constraints. The priorities are to develop decision tools at the farm and the regional levels, and to estimate the indirect effects of nitrogen on the environment du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 35 publications
0
27
0
7
Order By: Relevance
“…These farmers probably did not realise that the build-up of the harmful population of nematodes was related to the reduction in soil biodiversity caused by tillage (Clermont-Dauphin et al 2004 ). Meynard et al ( 2002 ) showed that farmers found it much easier to assess the economic performance of their production systems than their environmental performance. The environmental impacts of practices are often expressed on large geographical scales (catchment area, landscape) and long time scales (several years or even decades) that make it diffi cult to attribute them clearly to the individual practices of a given year.…”
Section: The Relationship Between Cropping Systems and Information Flowsmentioning
confidence: 99%
“…These farmers probably did not realise that the build-up of the harmful population of nematodes was related to the reduction in soil biodiversity caused by tillage (Clermont-Dauphin et al 2004 ). Meynard et al ( 2002 ) showed that farmers found it much easier to assess the economic performance of their production systems than their environmental performance. The environmental impacts of practices are often expressed on large geographical scales (catchment area, landscape) and long time scales (several years or even decades) that make it diffi cult to attribute them clearly to the individual practices of a given year.…”
Section: The Relationship Between Cropping Systems and Information Flowsmentioning
confidence: 99%
“…Principes g en eraux Nous nous sommes inspir es des concepts de d emarche qualit e et de management environnemental, d ej a eprouv es dans le cas de la gestion de l'azote en grandes cultures (Meynard et al, 2002). La d emarche suit le principe de « boucle de progr es », avec une r e evaluation r eguli ere des programmes de lutte en fonction des r esultats constat es et des actions mises en oeuvre, dans le but d'am eliorer la situation pas a pas.…”
Section: Conception Du Programme D'actions Et Du Tableau De Bordunclassified
“…Cette dépendance de l'outil à l'égard du SIC peut poser problème, car la maintenance de l'outil est coûteuse, et, dès qu'elle ne sera plus assurée, l'outil sera condamné. Comme le soulignent Meynard et al (2002), il serait souhaitable de conduire, dès la conception de l'outil, une réflexion sur la façon dont sa maintenance sera prise en compte dans les SIC. Ainsi, dans certains travaux récents, la facilité d'adaptation de l'outil à de nouvelles variétés a été placée en tête du « cahier des charges » lors de la conception : c'est le cas, par exemple, de l'outil BETHA (Loyce et al, 2001), qui vise à aider au choix de l'itinéraire technique du blé.…”
Section: Les Sic Et L'accompagnement De L'outilunclassified
“…En effet, cette dernière est guidée par les finalités : le conseiller choisit des situations pour construire un conseil adapté à leur diversité au sein de la petite région ; l'agriculteur, lui, cherche à évaluer la possibilité d'appliquer une « procédure de routine » ayant fait ses preuves (Cerf, 1996). Comment l'outil peut-il alors aider à construire ces procédures de routine et à reconnaître les situations où elles ne s'appliquent pas (Meynard et al, 2002) ?…”
Section: Enrichir L'anticipation Des Utilisateurs Des Usages Et Des unclassified